Macrocephaly-Capillary Malformation Syndrome in a Newborn With Tetralogy of Fallot and Sagittal Sinus Thrombosis. (January 2013) - Ercan, Tugba Erener; Oztunc, Funda; Celkan, Tiraje; Bor, Meltem; Kizilkilic, Osman; Vural, Mehmet; Perk, Yildiz; Islak, Civan; Tuysuz, Beyhan
Macrocephaly-capillary malformation syndrome is characterized by cutaneous vascular malformations with associated anomalies as macrocephaly, macrosomia, hemihypertrophy, hypotonia, developmental delay, lax joints, loose skin, polysyndactyly, and neuroimaging abnormalities. We present a newborn with a prenatal diagnosis of macrosomia and tetralogy of Fallot. He also had macrocephaly; a high forehead; capillary hemangioma on the forehead, upper lip, and philtrum; generalized loose skin; postaxial polydactyly of both hands and feet, with neuroimaging findings of polymicrogyria and thrombosis in sagittal sinus and sinus rectus. His condition was diagnosed as macrocephaly-capillary malformation syndrome in the neonatal period and he died suddenly during sleep at 6 months of age. The clinical course in this syndrome is not as benign as was previously thought. Careful follow-up of these patients with particular emphasis on neuroradiologic and cardiologic evaluation might help decrease the risk of sudden death and to improve long-term outcome.